Optimization of culture media and environmental conditions for somatic embryogenesis in olive (Olea europaea L.) cultivars ‘Arbequina’ and ‘Picual’ - Sebastián Agustín Bollati; José Pérez da Graça; Sonia Teresa Silvente; Vilma Cecilia Conci (Journal of the Saudi Society of Agricultural Sciences)
Abstract Somatic embryogenesis is a critical biotechnology for the clonal propagation and genetic improvement of Olea europaea L. However, its efficiency strongly depends on the culture medium composition and cultural conditions. This study aimed to optimize macronutrient formulations, photoperiod regimes, and induction durations for embryogenic callus development in the ‘Arbequina’ and ‘Picual’ cultivars. Three culture media (OMc, OMc1, and OMc2), differing in ionic composition, were evaluated. The results showed that OMc1 was the most effective medium, significantly increasing somatic embryo formation and callus weight in both cultivars. Principal Component Analysis (PCA) revealed that high concentrations of Ca2⁺ and Cl⁻, predominant in OMc, were negatively associated with embryogenic parameters, while NO₃⁻, NH₄⁺, and K⁺ showed strong positive correlations with explant survival, callogenesis, and embryo number particularly in OMc2. PCA further highlighted the contribution of Mg2⁺ and SO₄2⁻ to embryogenic rates, complementing the role of NO₃⁻, NH₄⁺, and K⁺ in callogenesis and biomass accumulation. Regarding environmental conditions, a 16/8 h light/dark photoperiod increased embryo number and callus biomass but reduced rhizogenic capacity compared to darkness (24 h). Moreover, longer induction periods (≥ 28 days) promoted callus proliferation while reducing embryogenic potential. These findings underscore the importance of multifactorial optimization in olive SE protocols and provide novel insights into the influence of ionic composition on regeneration responses. Adjusting media formulation, light exposure, and induction time can substantially improve the efficiency and reproducibility of somatic embryogenesis in olive cultivars.